Factores que limitan y favorecen la implementación del proyecto: “NosoTrans salud: Mujeres trans en situación de pobreza afirman el respeto a la identidad, libres de violencia, desde los servicios de salud. El caso Villa El Salvador” - Aguilar Salcedo, Brigitte Ana Lucia (2024)
The difficult and precarious situation of trans women in the country limits their access to healthcare; therefore, the risks regarding their life projects are influenced by the limited access to health, justice, and education services, among others. Consequently, the purpose of this study is to identify the factors that hinder and facilitate the implementation of the NosoTrans project in Villa El Salvador during the period of 2019-2021, analyzing the characteristics of the population, the project’s implementation strategies, and the follow-up of its actions. The study also examines the resources and communication channels, assessing the perception of social actors regarding the changes generated by the project, with the aim of formulating a proposal that allows for the successful and sustainable implementation of the project in Villa El Salvador. Promsex is a feminist non-governmental organization that promotes sexual and reproductive rights. Since 2019, it has implemented the NosoTrans project, seeking to strengthen advocacy for the respect of the human rights of transgender women in southern Lima. The project was carried out in Villa El Salvador and was supported by a committee composed of the trans women’s organization Féminas and the Association of Families for Sexual Diversity. This study adopts a human rights and community participation approach and is part of a case study. In this regard, it delves into the most relevant aspects of the experience itself, and for this reason, the research is applied and qualitative in nature. The most important findings and insights are as follows: i) strategic alliances with national and international entities, ii) a governance model based on comanagement processes, iii) capacity-building based on competencies, iv) permanent assistance from an advisory committee for decision-making, and v) the adaptability of the management team’s activities in response to the pandemic context. On the other hand, the research highlights some factors that limited the project’s implementation: i) the health emergency, and ii) the involvement of an external consultant, separate from the management team, which hindered the monitoring and follow-up process with healthcare personnel by the project team. Finally, from the critical perspective of social management, the thesis proposes an intervention model for projects involving trans women to ensure adequate access to healthcare.